Surimi and Low-Salt Surimi Gelation: Key Components to Enhance the Physicochemical Properties of Gels - Noman Walayat; María Blanch; Helena M. Moreno (Gels)
Surimi-based products are nutritionally valuable due to their essential amino acid composition, their content of high-quality proteins with excellent digestibility, and their low fat content. However, to achieve the desired texture, a significant amount of salt (1–3%) must be added, which could compromise their health benefits. This study provides an overview of surimi production, the gelation mechanism of myosin, and the most relevant gelation enhancers that could be used in manufacturing low-salt surimi-based products. Reducing the salt content in surimi-based products presents a significant challenge for the industry, not only from technological and sensory perspectives but also in response to the growing demand of consumers for healthier food options. So, this manuscript highlights several strategies for achieving optimal quality characteristics in relation to functional properties for the surimi products industry. In addition, surimi as a raw material is often misunderstood by consumers, who may question its nutritional value and, consequently, its consumption. Therefore, it is crucial to thoroughly explain the processing of this raw material and emphasize the importance of proper myofibrillar protein gelation to develop high-value surimi-based products.